Propafenone as potential AgoKir: exploration of long-term effects and mechanisms of propafenone on Kir2.1 channel. (10th June 2022) - Li, E; Kool, W; Woolschot, L; Van Der Heyden, MAG
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Chinese Scholarship Council Background: Inward rectifying potassium (Kir) channel expression and activity are tightly regulated within the heart. Kir channels play key roles in shaping cardiac action potentials, having a reduced conductance at depolarized potentials but contributing to the final stage of repolarization and resting membrane stability. The Kir2.1 channel protein has polyamine binding residues in both the transmembrane (D172) and the cytoplasmic domains (E224, E299), responsible for the process of inward rectification. A reduced functioning of Kir2.1 causes 1) Andersen-Tawil Syndrom and 2) is present in a subset of heart failure patients. Restoration of normal Kir2.1 function by agonists of Kir2.1 (AgoKirs) would be beneficial. The drug propafenone is identified as an AgoKir, but its long-term effects on Kir2.1 protein expression and subcellular localisation is unknown. Purpose: To investigate propafenone's long-term effect on Kir2.1 expression and its underlying mechanisms in cell systems. Methods: GFP, Dendra2 or non-tagged wildtype (WT) and mutant Kir2.1 expression constructs were transiently or stably (HEK-KWGF; CHO-KD cell lines) expressed in Human Embryonic Kidney and Chinese Hamster Ovary cells. Kir2.1 carried currents were measured by single cell patch clamp electrophysiology. Kir2.1 proteins expression levels were determined by Western blot analysis, whereas conventional immunofluorescence and advanced live-imaging microscopy were used to assess the subcellular localisation of Kir2.1 proteins. Propafenone was dissolved in DMSO, BaCl2 was used as Kir2.1 channel inhibitor. Results: Acute administration of 0.1 and 0.5 µM propafenone increased Kir2.1 carried outward current confirming the drug's Agokir status. Propafenone dose-dependently increased WT Kir2.1 expression levels (2.63±0.40 fold increase at 25 µM and 2.75±0.56 fold increase at 50 µM, 24h) in a process that is independent of the E224, E299 and D172 polyamine binding sites, and the R312 residue which is adjacent to the proposed propafenone binding site. Propafenone (25, 50 µM, 24h) induced intracellular accumulation of WT and mutant Kir2.1 proteins in the late endosome/lysosome compartment (Figure). Channel inhibition by BaCl2 did not affect the propafenone responses on Kir2.1 expression levels or subcellular localisation. Conclusion: Acute administration of propafenone at low concentrations increases Kir2.1 currents. Chronic propafenone treatment at only 25-100 times higher concentrations results in increased Kir2.1 protein expression levels and intracellular accumulation in late endosomes and/or lysosomes. Our data support the ability of propafenone at low concentrations to function as AgoKirs without disturbing Kir2.1 protein handing.